Cytological and histological findings of upper tract mucinous urothelial carcinoma with clear cell component: A case report and review of literature. Issue 5 (27th December 2021) - Kobayashi, Go; Uraoka, Naohiro; Sentani, Kazuhiro; Shibata, Jun; Nobuhiro, Ryosuke; Saito, Yoichi; Taniyama, Daiki; Hanamoto, Masanori; Nose, Hiroyuki; Oue, Naohide
Abstract: Mucinous urothelial carcinoma (UC) is a rare variant and only 18 cases of mucinous UC have been reported. In this article, we report a case of mucinous UC focusing on both cytological and histological findings. A 92‐year‐old female was referred to our hospital because of gross hematuria. Clinical computed tomography scan showed 2.2‐cm papillary lesion in the lower part of the left ureter. Urine cytology was performed, and cytopathological findings showed that there were a few atypical cells with pale to clear cytoplasm, and a low amount of mucin in the background was identified by periodic acid‐schiff (PAS) and alcian blue (AB) staining. Laparoscopic radical nephrectomy of left renal pelvis and ureter was performed. The gross examination revealed that a white‐gray, papillary‐sessile tumor was found in the lower part of the left ureter. Histologically, conventional high grade UC cells were seen in some areas, and tumor cells in other areas showed abundant clear cytoplasm with extracellular and intracytoplasmic mucin. Immunohistochemical analysis revealed that tumor cells were positive for CK7, CK20, p63, GATA3, MUC1, MUC2, and MUC5AC and negative for MUC6 and CDX2. Histopathological diagnosis was mucinous UC with clear cell component, and the pathological stage was pT1N0M0. The patient has remained well and disease‐free for 3 months after the operation. Familiarity and recognizing the characteristic pathological findings of mucinous UC are important because it represents a malignant neoplasm.